Assessing lower extremity stiffness in countermovement jumps: a critical analysis of the differences between calculation methods - Enqvist, J.; Holmberg, L. J.; Moberg, M.; Arndt, A. (Sports Biomechanics, 2024)
Introduction: Stiffness (k) describes a material`s resistance to deformation and is useful for understanding neuromuscular function, performance, and injury risk. The aim of this study is to compare the lower limb stiffness method (kLLS), which uses only force plate data, with methods combining force plate and motion capture data to calculate stiffness during the eccentric phase of a countermovement.